2007
DOI: 10.1108/13552540710750906
|View full text |Cite
|
Sign up to set email alerts
|

Optimization on selective laser sintering of metallic powder via design of experiments method

Abstract: Purpose -The objective of this study is to investigate the effect of various parameters on rapid prototyping parts for processes of sintering metallic powder by using Nd:YAG laser via the design of experiments (DOE) method. Design/methodology/approach -Experiments based on the DOE method were utilized to determine an optimal parameter setting for achieving a minimum amount of porosities in specimens during the selective laser sintering (SLS) process. Analysis of variance (ANOVA) was further conducted to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…The methodology is based on design of experiments [4] (DE) under two different scenarios: (1) considering 3DSystem and EOS technologies separately, (2) ana-lysing the two technologies into DE approach. Statistic calculation with ANOVA table was applied in both cases, showing the effects of different factors o n the variables (five factors and five variables).…”
Section: Methodol Ogymentioning
confidence: 99%
“…The methodology is based on design of experiments [4] (DE) under two different scenarios: (1) considering 3DSystem and EOS technologies separately, (2) ana-lysing the two technologies into DE approach. Statistic calculation with ANOVA table was applied in both cases, showing the effects of different factors o n the variables (five factors and five variables).…”
Section: Methodol Ogymentioning
confidence: 99%
“…Recently, it has been demonstrated that fine‐tuning the laser parameters may result in stabilization of the intended Fe 14 Nd 2 B phase with reduced (but still present) iron segregation for high cooling rates and the MQP‐S powder used . In general, microstructure and related properties of 3D printed (SLM) components are mainly influenced by processing parameters (laser power, laser scan velocity, laser scan grid space, substrate conditions, thickness of powder layer) and powder characteristics (particle shape, rheology, particle size, inner porosity, purity, humidity) …”
Section: Amount Of Occurring Phases (ϕ η Nd‐rich Oxides) Grain Simentioning
confidence: 99%
“…[5] In general, microstructure and related properties of 3D printed (SLM) components are mainly influenced by processing parameters (laser power, laser scan velocity, laser scan grid space, substrate conditions, thickness of powder layer) and powder characteristics (particle shape, rheology, particle size, inner porosity, purity, humidity). [8,9] In this paper, the feasibility of SLM using oxidation-sensitive permanent magnet Fe-Nd-B powder is demonstrated. In contrast to existing industrial methods for improving the grain size of Fe-Nd-B based sintered magnets, [10] the aim is to investigate a fundamental research approach.…”
mentioning
confidence: 99%
“…Response surface method is used to find out possible linear or non-linear relations between parameter levels and results generating regression analysis (Montgomery, 1997). Design of experiments (DOE) methods and some statistical analysis techniques were commonly used to achieve optimum solution at some various targets as in Miller et al (1997), Davim et al (2008), Song et al (2005), Yang et al (2002), Tarng and Yang (1998), Pan et al (2004), Liao and Shie (2007), Onwubolu et al (2007) and Chen et al (1996).…”
Section: Introductionmentioning
confidence: 99%